Covalently cross-linked tetrafunctionalized m-THPC chitosan hydrogels as drug delivery platforms - Gierlich, Piotr (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2022)
Photodynamic therapy (PDT) is an anti-cancer treatment method which uses the combined effect of a photosensitizing drug, light, and oxygen to cause selective damage to target tissue. The second generation photosensitizer (PS) 5,10,15,20-tetrakis(m- hydroxyphenyl)chlorin (m-THPC) is a widely characterized, clinically tested, and commercially available drug. In order to develop advanced treatment modalities, there is a need for improved drug delivery platforms. Hydrogels, which have been investigated as effective drug delivery systems (DDS), can prevent PSs aggregation due to their ability to swell in aqueous media. Chitosan (CS), a natural polysaccharide, is a suitable biodegradable material for hydrogel formulation and has been used in pharmaceutical applications. m-THPC was used as a starting point to prepare a library of compounds aimed at overcoming PS limitations while maintaining its clinical properties. Substitution, esterification, and Sonogashira coupling reactions were employed to append different functionalities at the periphery. Tetrafunctionalization of m-THPC allowed the linear photophysical properties and biological activity of the parent compound to be maintained, while improved optical properties suitable for application in two-photon induced PDT were also achieved. Next, the derivatives (PS 1, 3 and 5) were used as cross-linkers in the formation of CS hydrogels. Injectable, self- healing properties of hydrogels were confirmed macroscopically and by rheological analysis. Additionally, CS-based hydrogels allowed for pH-responsive drug release. m-THPC derivatives were tested in vitro against melanoma (B16F10) and colon carcinoma (CT26) cancer cells. The lead water-soluble m-THPC derivative (PS 3) was found to cause effective damage to cancer cells via lipid peroxidation in the absence of cellular internalization. Favourably, a lack of dark toxicity was also exhibited. In vivo biodistribution of the released PS from the hydrogel scaffold was studied using a fluorescence imaging technique to select the best drug-light interval (DLI) for the PDT treatment. The optimised PDT protocol allowed for a 67% survival rate against the CT26 tumor model and significantly extended the survival rate of melanoma tumor bearing mice. Moreover, due to prolonged release of the PS from the hydrogel scaffold, multiround light irradiation allowed enhanced stimulation of the immune system which was proved via three protocols: i) rechallenge of cured animals two months after PDT treatments, ii) evaluation of abscopal effects on a pseudo-metastatic model, and iii) evaluation of the PDT activity in immunocompetent versus immunocompromised mice. 75% of the mice rechallenged with CT26 cells exhibited cancer rejection. The treatment of only the primary tumor resulted in the abscopal protection against a secondary tumor. Finally, treatment of immunocompromised Balb/c nude mice did not result in efficient PDT confirming contribution of T cell mediated immunity to achieve an effective therapeutic response. Our therapeutic approach offers a new strategy to control not only primary but also metastatic tumors through local, intratumoral delivery of the PS3-based hydrogel and allows reduced side effect related with Foscan treatment.
APPROVED
Keywords: Photodynamic therapy; Hydrogel; Chitosan; m-THPC; Foscan; Photosensitizer